Risk Management in Mobile JKN Application at Depok Private Hospitals with FMEA Method - Riris Septiana Sita Dewi; Gerry Firmansyah; Agung Mulyo Widodo; Budi Tjahjono (Green Publisher Indonesia, 2025)
The Mobile JKN application that has begun to be implemented in every hospital is the main factor in the success of hospital services. Quite complete features are presented in one application. The variables measured in this study were occurrence (frequency of occurrence), severity (impact), and detectability (monitoring). The research data was obtained based on the results of direct observation at Bhakti Yudha Hospital. Risk management in the use of Mobile JKN is the main topic in this study. This study aims to assess information security risks using the FMEA method. The FMEA method is an error analysis method that arises from the design process of a design work. The results of this study are in the form of Risk Priority Number (RPN) values based on: severity (S = Severity), occurrence (O = Occurrence), and level of detectability (D = Detectability), and a report on risk management results which contains a list of risk analysis priorities accompanied by root causes of problems and risk control measures.